Jason Patrick Huska Photograph of Last Day on Campus during Shelter-in-Place - Huska, Jason Patrick::::::::: (2021)
A photograph of Jason Patrick Huska's last day on the San José State University campus when the Shelter-in-Place order took affect during Huska's senior year. Photograph taken by Emily Huska.